Pengaruh Perencanaan Keuangan Terhadap Efisiensi Manajemen Modal Kerja Pada UMKM Meichan Drink - Ajeng Mailani Dewi Pratiwi; Septia Khoerunnisa; Abdillah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Meichan Drink is a small and medium-sized enterprise (SME) engaged in soft drinks, focusing on innovation in taste and product quality. It was founded with the vision of providing a choice of quality, refreshing beverages to the public. The research method is a method of research that reduces research variables and operational definitions, sample determination, data types and sources, data collection methods, and analysis methods used. This chapter also explains that the research used a quantitative approach. Financial planning has a real and significant impact on the efficiency of working capital management at Meichan Drink. Although carried out simply and manually, consistent financial planning practices have helped this business manage fund usage, maintain smooth cash flow, and avoid unnecessary waste.